HUBUNGAN PENGGUNAAN KB SUNTIK HORMONAL 3 BULAN DENGAN SIKLUS MENSTRUASI DAN PENINGKATAN BERAT BADAN TEMPAT PRAKTEK MANDIRI BIDAN NI LUH SUKADANI, A.Md.Keb - Sukariyanti, Ni Luh Pande (STIKES ADVAITA MEDIKA TABANAN, 2026)
Abstract Intoduction: The family planning program is one of the five pillars of safe motherhood in the context of a strategy to reduce maternal mortality and morbidity. Hormonal injectable birth control is one of the most popular types of contraception among other contraceptives. The aim of this study was to determine the relationship between the use of hormonal birth control injections on the menstrual cycle and maternal weight gain. Metohds: This study used a cross sectional research design with accidental sampling, involving 75 family planning acceptors. Then data analysis was carried out with Spearman Runk because the data was not normally distributed. Suggestion: The research results showed that the majority of respondents had used injectable contraceptives for more than 2 years, namely 40 respondents (53.3%). Most respondents experienced irregular menstruation, namely 55 respondents (73.3%), while only 9 respondents used injectable contraceptives for 1-2 years with a regular menstrual cycle. Most respondents experienced an increase, namely 51 respondents (68%), while only 10 respondents used injectable contraceptives for 1-2 years and did not experience weight gain. There is a relationship between the use of injectable birth control and menstrual cycle disorders and weight gain. It is hoped that family planning acceptors can understand the effectiveness and side effects of injectable contraceptives as well as consideration in providing comprehensive midwifery care to injectable contraceptive acceptors. Keywords: birth control acceptors, menstrual cycle, weight gain